KAJIAN SEDIMENTASI DI SUB-DAS SEPARI DAS MAHAKAM KALIMANTAN TIMUR - Kuntadi Wibisono (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2018)
Sedimentation found in river flow is the result of erosion process that occurs within the watershed (Catchment area). The concentration of suspended load is one of the parameters observed from the watershed problem. Types of land use, land management, topography, rainfall, and soil type affect the river sedimentation conditions. The purpose of this research is to know the amount ofsedimentation in the Catchment Area of River Flow Control Station of Separi Sub-watershed which is part of the Mahakam Basin in Kutai Kartanegara Regency of East Kalimantan with an area of ± 23,578.07 Ha. Primary data consist of water level, instantaneous river flow velocity, and suspended load in 2017. Rating curve of river flow discharge and suspension discharge are made from instantaneous measurement. The results showed that the value of suspension discharge at the study site ± to 23,235.33 tons/year, or 0.99 tons/ha/ year which is included in the very low grade of ≤ 5 tons/ha/year. The presence of coal mining has no significant effect on sedimentation due to the processing of water flow in the mining area before entering the river. Low suspension discharge values are also caused by the dominant use of land in the form of plantations, as well as topographic conditions that are still in flat and sloping classes.